Bladder Acellular Matrix Prepared by a Self-Designed Perfusion System and Adipose-Derived Stem Cells to Promote Bladder Tissue Regeneration - Xiao, Shuwei; Wang, Pengchao; Zhao, Jian; Ling, Zhengyun; An, Ziyan; Fu, Zhouyang; Fu, Weijun; Zhou, Jin; Zhang, Xu (Frontiers in Bioengineering and Biotechnology, 2022)
The bladder patch constructed with the bladder acellular matrix (BAM) and adipose-derived stem cells (ASCs) was incubated with the omentum for bladder reconstruction in a rat model of bladder augmentation cystoplasty. A self-designed perfusion system and five different decellularization protocols were used to prepare the BAM. Finally, an optimal protocol (group C) was screened out by comparing the cell nucleus residue, collagen structure preservation and biologically active components retention of the prepared BAM. ASCs-seeded (BAM-ASCs group) and unseeded BAM (BAM group) were incubated with the omentum for 7 days to promote neovascularization and then perform bladder reconstruction. Hematoxylin and eosin and Masson's trichrome staining indicated that the bladder patches in the BAM-ASCs group could better regenerate the bladder wall structure compared to the BAM group. Moreover, immunofluorescence analyses demonstrated that the ASCs could promote the regeneration of smooth muscle, neurons and blood vessels, and the physiological function (maximal bladder capacity, max pressure prior to voiding and bladder compliance) restoration in the BAM-ASCs group. The results demonstrated that the self-designed perfusion system could quickly and efficiently prepare the whole bladder scaffold and confirmed that the prepared BAM could be used as the scaffold material for functional bladder tissue engineering applications.